Monitoring of the Track Geometry Quality Around the Portals of New Tunnel Construction Turecky Vrch - Preliminary Results - Libor Izvolt; Janka Sestakova; Michal Smalo; Zuzana Gocalova (Communications - Scientific letters of the University of Zilina, 2014)
At the beginning, the contribution deals with the characteristics of conventional structure (track skeleton placed in the ballast) and unconventional structure (slab track) of railway superstructure. The trial section is characterized in the next part where measurements of relative track geometry are made at regular intervals (spring and autumn) using continuous measuring device (manual measuring trolley KRABTM - Light). There is made the analysis of measurements made between 2012 - 2013 at the end of the contribution; with a view to assessing the quality of track geometry during particular sections monitored with in-built conventional and unconventional structure of railway superstructure. It also includes transition areas between these structures and an analysis of possible causes of variations in track geometry of modernized railway sections monitored.